A view of the learning organization from a corporate governance perspective: Interview with Bob Garratt. Issue 6 (10th September 2018) - Sidani, Yusuf; Reese, Simon
Abstract : Purpose: This paper aims to provide an overview of the development of learning organization concepts from the perspective of Professor Bob Garratt and presents an interesting evolution toward his work on learning boardroom members. Design/methodology/approach: Through a conversation with Professor Garratt, the authors capture several topics pertaining to his evolution of learning organization concepts, those who have differing views and ultimately what led him to develope his theories on the impact of the most senior members of an organization on the learning constructs. Findings: The learning organization debate has many foundations that today have led to differing perspectives. Professor Garratt provides his particular background and how he developed his opinions, which he admits have not always been embraced in practice. Originality/value: The discussion with Bob Garratt reveals his understanding of the learning organization concept and how it developed from a lifetime of practical application. Ultimately, the reader will understand, in Professor Garratt's own words, where he was confronted with challenges and why his concepts evolved to where they are today.